2021
DOI: 10.3390/polym13152462
|View full text |Cite|
|
Sign up to set email alerts
|

Decarbonising the Portland and Other Cements—Via Simultaneous Feedstock Recycling and Carbon Conversions Sans External Catalysts

Abstract: The current overarching global environmental crisis relates to high carbon footprint in cement production, waste plastic accumulation, and growing future energy demands. A simultaneous solution to the above crises was examined in this work. The present study focused on decarbonizing the calcination process of the cement making using waste plastics and biowastes as the reactants or the feedstock, to reduce the carbon footprint and to simultaneously convert it into clean energy, which were never reported before.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Another study by Pravin et.al [ 33 ] accomplished the conversion of PE (polyethylene) to syngas through pyrolysis then gasification using Aspen plus. The results were not validated by the experiment due to the lack of resources; however, they claimed that the most convenient temperature, and equivalence ratio for the pyrolysis unit were 0.4–0.6, and 500–750 , respectively The catalytic approach has advantages over the thermal one in terms of reducing the sulfur content when special catalysts are used (i.e., CaS, and MgS) [ 34 , 35 , 36 ]. Several studies have been performed on the conversion of waste plastics to hydrogen along with other feedstocks [ 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another study by Pravin et.al [ 33 ] accomplished the conversion of PE (polyethylene) to syngas through pyrolysis then gasification using Aspen plus. The results were not validated by the experiment due to the lack of resources; however, they claimed that the most convenient temperature, and equivalence ratio for the pyrolysis unit were 0.4–0.6, and 500–750 , respectively The catalytic approach has advantages over the thermal one in terms of reducing the sulfur content when special catalysts are used (i.e., CaS, and MgS) [ 34 , 35 , 36 ]. Several studies have been performed on the conversion of waste plastics to hydrogen along with other feedstocks [ 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, in the quest to convert carbon into sustainable energy sources like hydrogen and syngas, the utilization of plastics and biowastes holds the potential to reduce the environmental impact of industrial processes found in sectors such as iron, steel, and cement [9] [10]. The co-gasification of mixtures containing plastic and biomass, achieved through dry and steam reforming of CO2, results in the production of H2, with factors such as feed composition and catalyst selection influencing the conversion of waste plastics into valuable fuel products [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The co-gasification of mixtures containing plastic and biomass, achieved through dry and steam reforming of CO2, results in the production of H2, with factors such as feed composition and catalyst selection influencing the conversion of waste plastics into valuable fuel products [11][12][13][14][15]. Various variables, including temperature, the ratio of polymers to biomass, CO2/CH4 ratios, and the choice of catalyst, all contribute to the H2 production process [9][16]- [18]. Waste polymers like polyethylene and polypropylene exhibit low moisture and ash contents but possess high volatile content, viscosity, and heating value.…”
Section: Introductionmentioning
confidence: 99%
“…While simultaneously transforming carbon into sustainable energy sources such as hydrogen and syngas, the utilization of plastics and biowastes can reduce the environmental impact of industrial processes found in sectors like iron steel, and cement [8] [9]. The cogasification of plastic and biomass mixtures through dry and steam reforming of CO2 generates H2, with factors like feed composition and catalyst type influencing the conversion of waste plastics into fuel products [10] [11].…”
Section: Introductionmentioning
confidence: 99%